Aufarbeitung der Pandemie und Bedenken der Impfbereitschaft: Auswirkungen individueller Aufklärungsgespräche vor der COVID-19-Impfung - Wüller, Moritz; Grotemeyer, Alexander; Thürauf, Norbert (Prävention und Gesundheitsförderung, 2025)
Background: The availability of vaccinations against SARS-COV‑2 was also accompanied by vocal opposition to the preventive measure. There was a trend among medical staff to reject the vaccination and the question of mandatory vaccination was discussed politically. What concerns and fears exist before and after vaccination and how can these be reduced? Is it possible to provide information in a way that is appropriate for the target group? Goals: The aim of this paper is to better adapt the educational discussion to the wishes and possible concerns of the person to be vaccinated. To achieve this, it is necessary to recognize influencing factors in the decision-making process and to identify important aspects of different groups. Methods: A questionnaire on the topic of COVID vaccination was created following a literature review of the authors’ experiences. This was sent to employees of the Psychiatry Department of the University Hospital Erlangen via an online survey from May to July 2021. Office programs helped with the evaluation and the statistics were created with Prism9 (GraphPad, Boston, MA, USA). Results: We found that the acceptance rate of vaccination was 97%. 83% requested the personal consultation/educational talk; 17% were unsure about vaccination and benefited from personal consultation/education. It could be shown that decisions already made about vaccination were not influenced by the vaccination discussion. Conclusion: It was shown that decisions already made about vaccination were not influenced by the vaccination discussion. This study shows not only the influence of personal education, but also the necessity of such a discussion in advance. The level of education plays a decisive role in the provision of information.
CRIS-Team Scopus Importer:2025-02-17
Keywords: COVID-19 vaccine; Decision making (informed); Effective communication; Personal interview; Preventive medicine

Therapierefraktäre erstmalige Depression im mittleren Lebensalter - Grotemeyer, Alexander; Kornhuber, Johannes; Spitzer, Philipp (Der Nervenarzt, 2023)
CRIS-Team Scopus Importer:2023-09-22